EXPORT/IMPORT PROCEDURES and DOCUMENTATION - Bade, Donna L. (American Management Association, 2015)
International business is more complex today than ever before. Customs and export control requirements, distributors versus agents, payment mechanisms, insurance, transportation. Even the most seasoned professionals can find themselves in need of guidance through this never-ending sea of rules, regulations, and paperwork--for multiple countries!Featuring dozens of sample contracts, procedures, checklists, and ready-to-use forms, Export/Import Procedures and Documentation is an authoritative voice in the ever-changing, often-confusing world of international laws and regulations. The revised fifth edition contains new and expanded information on topics including: · Corporate oversight and compliance· Valuation· The Export Control Reform Act· Licensing requirements and exceptions· International Commerce Trade Terminology· The shifting definition of "Country of Origin"· Specialized exporting and importing· And moreYou no longer have to worry about all the dos, don'ts, and details of the vast world of importing/exporting. This all-in-one global-business resource has done it for you already.